Amoxicillin-metronidazole association compared with ampicillin in the management of premature rupture of membranes in pregnancies preterm - Santos, José (2015)
Objective: To compare the efficacy of two antibiotic regimes for premature rupture of the membranes. Design: Sixty one patients were divided in two groups with similar age and parity, gestational age between 28 and 37 weeks, who experienced premature rupture of membranes. Two therapeutical regimes were administered consisting in oral amoxicillin 500 mg every 6 hours plus oral metronidazol 500 mg every 8 hours (scheme A) in 31 patients, and ampicillin 500 mg every 6 hours, in 30 patients (scheme B). Results: Average age was 25 years, parity 2, gestational age 34 weeks, nulliparity 52,36%. The shortest and longest latency periods were 3 and 21 days for group A and 1 and 14 days for group B. Irregularities in the treatment and mobilization of patients significantly changed the results. Conclusions: Latency for scheme A was longer than for scheme B (8 days vs. 4,6 days). Mobilization and irregular treatment had a negative influence in both treatments.